O origami como recurso pedagógico no ensino de matemática no ensino fundamental - Souza, Milena Cardozo de (Universidade Federal de São Carlos, 2026)
The use of origami as a pedagogical resource in Mathematics classes provides several benefits for expanding geometric knowledge, as it allows students to visualize and manipulate abstract concepts in a concrete way. By making folds, it is possible to explore plane and spatial figures, angles, symmetries, areas, perimeters, as well as relationships between shapes, which facilitates the understanding of content often considered difficult. In addition, origami stimulates logical reasoning, concentration, and motor coordination, making learning more dynamic, playful, and enjoyable. This practice also contributes to the development of creativity and patience in problem-solving, while promoting interdisciplinarity by bringing Mathematics closer to artistic and cultural aspects. In this way, origami proves to be a valuable teaching resource for transforming the classroom into a space for meaningful knowledge construction. This project aims to implement the practice of origami in the classroom, continuing a previous work on the same theme, which was the author’s undergraduate thesis completed in 2007. In this new stage, the ideas presented in the earlier work were effectively applied in the classroom, integrating theory and practice. To broaden the experience, some activities were carried out in groups, in which each team built a figure and then explained which geometric concepts were applied. Another possibility was organizing challenges, such as creating specific shapes using only certain folds, encouraging problem-solving. At the end, an exhibition of the productions took place, showing how Mathematics and art interact through origami. This approach not only strengthens geometric content but also makes classes more interactive, collaborative, and meaningful.
Origami as a pedagogical resource in teaching mathematics in elementary school
Keywords: Origami; Ensino fundamental; Matemática; Recurso pedagógico; CIENCIAS EXATAS E DA TERRA::MATEMATICA; 4. Educação de Qualidade